Improved electrochemical performance of Mn3O4 thin film electrodes for supercapacitors. (September 2018) - Shaik, Dadamiah P.M.D.; Rosaiah, P.; Ganesh, K. Sivajee; Qiu, Yejun; Hussain, O.M.
Abstract: Fabrication of the Mn3 O4 thin film electrodes is an important area of research for the development of supercapacitors. Investigations were made to improve the electrochemical properties of the electron beam evaporated Mn3 O4 films. The films grown on stainless steel substrates at a substrate temperature of 473 K with subsequent annealing at 573 K for 4 h were in a single phase, which corresponds to the tetragonal structure of Mn3 O4 with I 41/ amd (141) space group. The Raman studies were also confirmed the single phase of Mn3 O4 films. The AFM data revealed that the surface of the films covered with dispersed vertical grains of size 36 nm with the rms surface roughness of 18 nm. The SEM image displayed the flower like growth of Mn3 O4 on the substrate. The films deposited at 573 K exhibited a specific capacitance of 568 F g −1 at a current density of 1 A g −1 in 1 M Na2 SO4 aqueous electrolyte with excellent capacitance retention of 93% even after 5000 cycles. The films annealed above 600 K were found to have mixed phases and corresponding capacitance decreased with annealing temperatures. The films annealed at 773 K exhibited only Mn2 O3 phase with a lower specific capacitance of 240 F g −1 .